Accounting Quality and Managerial Incentives for Voluntary Disclosure - Zang, Yoonseok (Institutional Knowledge at Singapore Management University, 2008)
The central focus of this paper is on how the quality of anticipated mandatory accounting reports affects the bias in and likelihood of voluntary management disclosures. Our model integrates two paradigms used to analyze management disclosures, those in which managers choose to disclose or not when disclosures must be truthful, and those in which managers choose the extent of bias when disclosures always occur. Thus, we incorporate both proprietary (firm-wide) costs of disclosures and personal costs of biasing. In our model, the manager endogenously determines both whether to disclose and, if disclosure occurs, how much to bias the disclosure. We find that increases in the quality of mandatory accounting reports decrease the bias in management disclosures because investors rely relatively less on the disclosures in determining the firm’s value. Further, as the quality of accounting reports increases, the probability of management disclosures also increases because the cost to the manager of biasing the disclosures decreases. Finally, we show that the manager may prefer low to high quality mandatory accounting reports when the proprietary costs of disclosures are large or the manager’s stock-based incentives are large relative to the personal cost of biasing.